2003
DOI: 10.1385/endo:20:1-2:59
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-Releasing Peptide and Its Homolog RFRP-1 Act in Hypothalamus but Not in Anterior Pituitary Gland to Stimulate Stress Hormone Secretion

Abstract: The RF-amide peptides (RFRPs), including prolactin (PRL)-releasing peptide-31 (PrRP-31) and RFRP-1, have been reported to stimulate stress hormone secretion by either direct pituitary or indirect hypothalamic actions. We examined the possible direct effects of these peptides on PRL and adrenocorticotropin (adrenocorticotropic hormone [ACTH]) release from dispersed anterior pituitary cells in culture and on PRL and ACTH secretion following intracerebroventricular (i.c.v.) administration in vivo. Neither peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 25 publications
3
36
1
Order By: Relevance
“…It now appears unlikely that PrRP stimulates prolactin release in vivo (Taylor & Samson 2001), despite there being evidence that PrRP is involved in regulating the secretion of other hypothalamopituitary factors, including corticotrophin-releasing hormone, follicle-stimulating hormone (FSH) and luteinising hormone (LH), and oxytocin (Maruyama et al 1999b, Hizume et al 2000, Samson et al 2003.…”
Section: Prrp Familymentioning
confidence: 99%
See 1 more Smart Citation
“…It now appears unlikely that PrRP stimulates prolactin release in vivo (Taylor & Samson 2001), despite there being evidence that PrRP is involved in regulating the secretion of other hypothalamopituitary factors, including corticotrophin-releasing hormone, follicle-stimulating hormone (FSH) and luteinising hormone (LH), and oxytocin (Maruyama et al 1999b, Hizume et al 2000, Samson et al 2003.…”
Section: Prrp Familymentioning
confidence: 99%
“…Our own studies suggest that both RFRP-1 and -3 have the ability to modify feeding in rats and mice when administered centrally (unpublished observations). ICV administration of RFRP-1 to rats has also been shown to raise circulating levels of prolactin in a concentration-dependent manner, without an observable effect on circulating growth hormone (GH), LH, FSH, thyrotrophin-and adrenocorticotrophin-releasing hormone levels , Samson et al 2003. However, RFRP-1 was not able to elicit the release of prolactin from dispersed anterior pituitary cells, and its ability to increase prolactin in vivo was attenuated in rats pre-treated with the dopamine D2 receptor blocker, domperidone (Samson et al 2003).…”
Section: Lpxrfamide Familymentioning
confidence: 99%
“…In mammals, Hinuma et al (2000) have found that the deduced human LPXRF-amide peptide, human RFRP-1, increased prolactin release in the rat. Another group has also reported the stimulatory effect of RFRP-1 on prolactin release (Samson et al 2003). Hinuma et al (2000) have further reported the receptors for rat and human RFRP, which were G protein-coupled receptors (GPCRs).…”
Section: Introductionmentioning
confidence: 99%
“…GPR10, also known as the prolactin releasing hormone receptor (PRLHR), is the receptor for prolactin releasing peptide (PrRP), although evidence for its specific role in pituitary PRL production is tenuous (16,17). Normal expression and function of GPR10 have been shown to be limited to several regions of the hypothalamus (18,19). The mechanism of hypothalamic GPR10 action that evokes stress hormone release (19) from the pituitary is not well understood and its function in the periphery, either in normal tissues or in disease, has not been reported.…”
mentioning
confidence: 99%
“…Normal expression and function of GPR10 have been shown to be limited to several regions of the hypothalamus (18,19). The mechanism of hypothalamic GPR10 action that evokes stress hormone release (19) from the pituitary is not well understood and its function in the periphery, either in normal tissues or in disease, has not been reported. The nearubiquitous overexpression of GPR10, a normally neuronal specific G protein coupled receptor (GPCR), in human leiomyomas is unparalleled among genes shown to be dysregulated in fibroids.…”
mentioning
confidence: 99%